Comparative Bioavailability of Sulindac in Capsule and Tablet Formulations - Reid, Joel M. (2008)
The cyclooxygenase-2 (COX-2) enzyme appears to be an important target for cancer chemoprevention. Given the recent emergence of potentially serious cardiovascular toxicity associated with selective COX-2 inhibitors, nonsteroidal antiinflammatory drugs (NSAIDs), which inhibit both COX-1 and COX-2, have received renewed attention as candidate chemoprevention agents. Sulindac has demonstrated consistent chemopreventive potential in preclinical studies, as well as in a limited number of clinical trials reported to date. For the current pharmacokinetic study, sulindac capsules were prepared to facilitate ample agent supplies for future intervention studies. Encapsulation of the parent compound (sulindac sulfoxide) can be readily accomplished, but the effects of alternate formulations on bioavailability have not been rigorously examined. In the present single-dose, two-period crossover trial, we conducted pharmacokinetic analyses of sulindac in capsule (test) versus tablet (reference) formulations. Overall, bioavailability appeared to be higher for the capsule compared to the tablet formulation, based on test-to-reference pharmacokinetic parameter ratios for the parent compound. However, additional analyses based on the sulfide and sulfone metabolites of sulindac with the same pharmacokinetic parameters indicated similar chemopreventive exposures between the capsule and tablet formulations. These data support the use of sulindac capsules, which can be readily prepared with matching placebos, in future blinded chemoprevention trials.